Spillover effects of foreign hypermarkets on domestic suppliers in Malaysia - Kaliappan, Shivee Ranjanee; Alavi, Rokiah; Abdullah, Kalthom; Zakaullah, Muhammad Arif (Emerald Group Publishing Limited, 2009)

(untitled)
Purpose – Since the mid-1990s, there has been a rapid expansion of large-scale foreign retailers in many countries across Southeast Asia, Central Europe and Latin America. This emerging trend has triggered a number of research interests on the issue of retail globalization. The research aims to consider the entry of foreign hypermarkets in Malaysia and their impact on the development and growth of domestic suppliers and manufacturers.